Mitochondrial Superoxide Production Decreases on Glucose-Stimulated Insulin Secretion in Pancreatic β Cells Due to Decreasing Mitochondrial Matrix NADH/NAD+ Ratio - Plecitá-Hlavatá, Lydie; Engstová, Hana; Holendová, Blanka; Tauber, Jan; Špaček, Tomáš; Petrásková, Lucie; Křen, Vladimír; Špačková, Jitka; Gotvaldová, Klára; Ježek, Jan; Dlasková, Andrea; Smolková, Katarína; et al. (Antioxidants & redox signaling, 2020)
Aims: Glucose-stimulated insulin secretion (GSIS) in pancreatic β cells was expected to enhance mitochondrial superoxide formation. Hence, we elucidated relevant redox equilibria. Results: Unexpectedly, INS-1E cells at transitions from 3 (11 mM; pancreatic islets from 5 mM) to 25 mM glucose decreased matrix superoxide release rates (MitoSOX Red monitoring validated by MitoB) and H2O2 (mitoHyPer, subtracting mitoSypHer emission). Novel double-channel fluorescence lifetime imaging, approximating free mitochondrial matrix NADHF, indicated its ∼20% decrease. Matrix NAD+F increased on GSIS, indicated by the FAD-emission lifetime decrease, reflecting higher quenching of FAD by NAD+F. The participation of pyruvate/malate and pyruvate/citrate redox shuttles, elevating cytosolic NADPHF (iNAP1 fluorescence monitoring) at the expense of matrix NADHF, was indicated, using citrate (2-oxoglutarate) carrier inhibitors and cytosolic malic enzyme silencing: All changes vanished on these manipulations. 13C-incorporation from 13C-L-glutamine into 13C-citrate reflected the pyruvate/isocitrate shuttle. Matrix NADPHF (iNAP3 monitored) decreased. With decreasing glucose, the suppressor of Complex III site Q electron leak (S3QEL) suppressor caused a higher Complex I IF site contribution, but a lower superoxide fraction ascribed to the Complex III site IIIQo. Thus, the diminished matrix NADHF/NAD+F decreased Complex I flavin site IF superoxide formation on GSIS. Innovation: Mutually validated methods showed decreasing superoxide release into the mitochondrial matrix in pancreatic β cells on GSIS, due to the decreasing matrix NADHF/NAD+F (NADPHF/NADP+F) at increasing cytosolic NADPHF levels. The developed innovative methods enable real-time NADH/NAD+ and NADPH/NADP+ monitoring in any distinct cell compartment. Conclusion: The export of reducing equivalents from mitochondria adjusts lower mitochondrial superoxide production on GSIS, but it does not prevent oxidative stress in pancreatic β cells.
Keywords: energetický metabolismus; flavinadenindinukleotid; pancreatic β cells; Chromatography, Liquid; Mitochondria; adenosintrifosfát; Flavin-Adenine Dinucleotide; Glucose; kyselina citronová; fluorescence lifetime imaging; NAD; Superoxides; superoxidy; Metabolomics; Cell Respiration; glucose-stimulated insulin secretion; metabolomika; buněčné dýchání; Membrane Potential, Mitochondrial; signální transdukce; Citric Acid; peroxid vodíku; glukosa; Mass Spectrometry; Hydrogen Peroxide; chromatografie kapalinová; Signal Transduction; NADH/NAD+ ratio; krysa rodu Rattus; Animals; sekrece inzulinu; Energy Metabolism; zvířata; beta-buňky; metabolické sítě a dráhy; Rats; Adenosine Triphosphate; membránový potenciál mitochondrií; Insulin-Secreting Cells; mitochondrial superoxide generation; hmotnostní spektrometrie; Complex I; Metabolic Networks and Pathways; Insulin Secretion; mitochondrie